PENGEMBANGAN SISTEM KENDALI OTOMATIS PROSES RECHARGING TINTA SPIDOL WHITEBOARD - Khairudin, M.; Ridho, R.N. (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Control system on the recycle process of markers ink aims to control charging ink on the recycle process of whiteboard markers ink. The process of opening the lid will automatically proceed with the charging process of whiteboard ink. The objectives of this tool are to control the time of ink charging using the solenoid. Solenoid control using the minimum system of microcontroller. The hardware consists of a circuit of microcontroller of ATmega16, driver of solenoid valve using L298 IC, push button, power supply and mechanics for opening and closing markers. It is expected this system can help the process of ink recharging automatically on the whiteboard markers. The performances of lever cap on the recycle process of markers ink show proper performance. The system can fill ink to the markers accordance with the planning. The volume of the markers ink with capacities of up to 25% with the ink discharge of 0,003 liters / second. The system has an average of percentage error of less than 2% of the measured voltage.